Nonce Words-Formation in Indonesian Online Newspapers - Merry Lapasau; Sulis Setiawati; Tio Zulfan Amri (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
The present study attempts to analyze the word-formation of nonce words usually used by the youth and the function of its usage in online newspapers in Indonesia. This research used a descriptive qualitative approach. Research objects were nonce words in the form of basic words and phrases in various texts in online newspapers between March to September 2020 as many as 15 samples. The result of the study shows that the usage of nonce words in online newspapers in Indonesia can still be said to be marginal and nonce words appear mostly in headlines and less in body text because the language of the newspaper has its characteristics and is tied to the rules of the language of the mass media. The function of nonce words in online newspapers corresponds to the criteria of Heyne and Vollmer (2016) which are textual, stylistic, and reference. Nonce words in the form, and meaning, or both with novel values, are created from different needs and are used in various areas of communication. The formation of nonce words reflects the social conditions that are determined by developments in a country.Keywords: Nonce words; language of newspapers; word-formation; Indonesian